A homotopy analysis method for the nonlinear partial differential equations arising in engineering. Issue 2 (4th May 2017) - Hariharan, G.
ABSTRACT: In this article, we have established the homotopy analysis method (HAM) for solving a few partial differential equations arising in engineering. This technique provides the solutions in rapid convergence series with computable terms for the problems with high degree of nonlinear terms appearing in the governing differential equations. The convergence analysis of the proposed method is also discussed. Finally, we have given some illustrative examples to demonstrate the validity and applicability of the proposed method.